Postoperative Evaluation of Changes in Extracranial-Intracranial Bypass Graft Using Superficial Temporal Artery Duplex Ultrasonography - Nakamizo, A.; Inoue, T.; Kikkawa, Y.; Uda, K.; Hirata, Y.; Okamura, K.; Yasaka, M.; Okada, Y. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Extracranial-intracranial (ECIC) bypass grafts have been assessed postoperatively by various neuroradiologic techniques. The aim of this prospective study was to evaluate postoperative changes in ECIC bypass graft by using superficial temporal artery duplex ultrasonography (STDU). Furthermore, this study assessed the ability of STDU to predict cerebrovascular reserve capacity (CVR).MATERIALS AND METHODS: Forty-five consecutive patients who underwent ECIC bypass procedure for atherosclerotic internal carotid artery occlusion were enrolled in this prospective study. All patients underwent single-photon emission CT and STDU preoperatively, 14 days after, 3 months after, 1 year after, and 2 years after ECIC bypass.RESULTS: The diameter and flow velocities of the ipsilateral superficial temporal artery (STA), and regional cerebral blood flow (rCBF) showed increase during the first 2 weeks and then remained stable, whereas CVR showed a constant improvement up to 2 years after surgery. The STA diameter and mean STA flow velocity correlated significantly with CVR at 1 year after surgery (r 2 = 0.1232 and r 2 = 0.08716, respectively; P < .05). A cutoff value of 1.8 mm STA diameter was determined as the most reliable value to predict CVR greater than 10% at 1 year after surgery. The positive predictive value was calculated as 96.6%, the negative predictive value as 43.8%, the sensitivity as 75.7%, the specificity as 87.5%, and the likelihood ratio as 6.056.CONCLUSIONS: ECIC bypass grafts can be assessed postoperatively in a noninvasive fashion with STDU. This technique provides information regarding patency as well as quantitative assessment of bypass function. Moreover, STDU is useful to predict CVR improvement.